1996
DOI: 10.1590/s0074-02761996000100002
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of malaria in Prábis, Guinea-Bissau

Abstract: This article reports upon a community survey of malaria in Prábis, Guinea-Bissau. A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In keeping with this, an active case detection cohort demonstrated no agedependence of malarial disease and a maximal parasite prevalence of only 25% in 4 year olds . Variations in malaria transmission have been described elsewhere (Cattani et al 1986;Goncalves et al 1996;Browne et al 2000;Clarke et al 2002) and, in Kilombero, are likely to be due to a combination of differentials in vector breeding site densities, access to curative treatment from health facilities and shops and the use of insecticide-treated mosquito nets (Drakeley et al 2003). However, in recent years we observed that the pattern of malaria transmission within the ISA itself was changing.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In keeping with this, an active case detection cohort demonstrated no agedependence of malarial disease and a maximal parasite prevalence of only 25% in 4 year olds . Variations in malaria transmission have been described elsewhere (Cattani et al 1986;Goncalves et al 1996;Browne et al 2000;Clarke et al 2002) and, in Kilombero, are likely to be due to a combination of differentials in vector breeding site densities, access to curative treatment from health facilities and shops and the use of insecticide-treated mosquito nets (Drakeley et al 2003). However, in recent years we observed that the pattern of malaria transmission within the ISA itself was changing.…”
Section: Introductionsupporting
confidence: 59%
“…Variations in malaria transmission have been described elsewhere (Cattani et al. 1986; Goncalves et al. 1996; Browne et al.…”
Section: Introductionmentioning
confidence: 99%
“…The country has been considered as mesoendemic-to-holoendemic with intense and seasonal transmission during the rainy season. 23,24 Anopheles gambiae s.s. and Anopheles melas are the main malaria vectors in the area. 25 Sampling took place at the end of the rainy season in 2 consecutive years, 1995 (October) and 1996 (November).…”
Section: Study Area and Sample Collectionsmentioning
confidence: 99%
“…In the Cacheu region in the north-western part of the country a study found parasite rates in children aged 2 to 9 years of 44 % -79 %, suggesting malaria to be mesoendemic to hyperendemic (85). In a village just outside Bissau the level of endemicity varied from hypo-to holoendemic with closeness to rice fields being one of the important determinants for parasitaemia (60).…”
Section: Malaria Endemicitymentioning
confidence: 99%